The bahamas project: effects of a running scalar spectral index on large-scale structure. Issue 1 (20th January 2020) - Stafford, Sam G; McCarthy, Ian G; Crain, Robert A; Salcido, Jaime; Schaye, Joop; Font, Andreea S; Kwan, Juliana; Pfeifer, Simon
ABSTRACT: Recent analyses of the cosmic microwave background (CMB) and the Lyman α forest indicate a mild preference for a deviation from a power-law primordial matter power spectrum (a so-called running). We introduce an extension to the bahamas suite of simulations to explore the effects that a running scalar spectral index has on large-scale structure (LSS), using Planck CMB constraints to initialize the simulations. We focus on five key statistics: (i) the non-linear matter power spectrum (ii) the halo mass function; (iii) the halo two-point autocorrelation function; (iv) total mass halo density profiles; and (v) the halo concentration–mass relation. We find that the matter power spectrum in a Planck -constrained running cosmology is affected on all k -scales examined in this study. These effects on the matter power spectrum should be detectable with upcoming surveys such as LSST and Euclid . A positive running cosmology leads to an increase in the mass of galaxy groups and clusters, with the favoured negative running leading to a decrease in mass of lower mass (M 10^13 M_ ) haloes, but an increase for the most massive (M 10^13 M_ ) haloes. Changes in the mass are generally confined to 5-10 per cent which, while not insignificant, cannot by itself reconcile the claimed tension between the primary CMB and cluster number counts. We also demonstrate that the observed effects on LSS due to a running scalar spectral index are separable from those of baryonic effects to typically a few per cent precision.